A non-invasive technique to monitor reproductive hormone levels in common palm civets, Paradoxurus hermaphroditus Pallas, 1777 - Hien, Nguyen Thi Thu; Thao, Nguyen Thi Phuong; Binh, Nguyen Thanh (Academia Journal of Biology, 2018)
Fecal steroid assays have been used to provide information on the estrous cycle, pregnancy, re-estrus, reproductive season and therapeutic treatments of an expanded list of species. This same method could be used in monitoring the reproductive status of the common palm civets (Paradoxurus hermaphroditus), also called toddy cats, a nocturnal omnivorous mammal found in South east Asia in general and Vietnam in particular. To study its reproductive cycles, we have collected 2,635 fecal samples from 12 adult female civets in captivity at Dong Nai Biotechnology Center. Progesterone (P4) and Estradiol (E2) contents from fecal samples were analyzed using automatic ELISA Dynex DS2 and the Progesterone and Estradiol ELISA Kit. In non-pregnant civets, the concentrations of fecal E2 ranged from 0.05 to 7.01 μg/g dry feces (df), with the average of 1.07 ± 0.84 μg/g and a peak of 3.22 ± 0.64 μg/g. Fecal progesterone metabolites ranged from 0.15 to 12.32 μg/g, and the overall mean of the samples was 1.72 ± 2.16 μg/g. The average period of change in E2 content was 28.6 ± 2.29 days. During pregnancy, the P4 content in the stool ranged from 6.21 to 23.12 μg/g with the average of 15.17 ± 5.22 μg/g, which was approximately 5 to 7 fold higher than that of non-pregnant animals (p < 0.05). In pseudopregnancy civets, there were also significant changes in P4 after fertilization, but the duration was only a half of the pregnant length. The P4 concentration in the stool at this stage ranged from 8.02 to 11.47 μg/g, an average of 9.73 ± 1.73 μg/g. This index was also significantly higher in non-pregnant and statistically different from those in pregnant (p < 0.05). It was found that fecal hormone metabolite analysis is a useful and reliable indication to confirm estrous cycle, pregnancy, non-pregnancy or presumed pseudopregnancy of P. hermaphroditus, both in the wild and in captivity.